Midwife Led Units: Transforming Maternity Care Globally - Joyce K. Edmonds; Juliana Ivanof; Urusala Kafulafula (Ubiquity Press, 2020)
Background: Midwifery-led care is a high-certainty, evidence-based strategy to improve maternity care. Midwife-led units (MLUs) are one example of how the midwifery model of care is being integrated into existing health systems to transform maternal health around the world. Purpose: To promote global investment in MLUs by describing the benefits, current advances and future directions of this model of care. Method: A viewpoint based on prevalent notions of midwifery, research findings, guidance from professional organizations and authors' professional experience. Conclusion: Renewed commitment to research and the implementation of MLUs across a variety of settings is needed to address the practice, education and policy issues associated with this evidence-based strategy. The World Health Organization "Year of the Nurse and Midwife-2020" is an opportune time to invest in midwifery models of care that are fundamental to achieving core global health initiatives such as Universal Healthcare 2030.